The effect of addition red ginger (Zingiber Officinale Var. Rubrum) and garlic (Allium sativum L ) to salted egg quality with the dry curing method - Puji Astuti; Ramadhan, Ridho Wahyu; Fitroh, Bagus andika; Putri Awaliya Dughita (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This research aims to know the effect addition of red ginger and garlic to salted egg quality with dry curing method. This research used 160 fresh duck eggs which were curing for 14 days with a mixture of red ginger and garlic with 4 treatments that is P0 (without red ginger and garlic (control)), P1 (addition of red ginger 80% and garlic 20%), P2 (addition of red ginger 50% and garlic 50%), P3 (addition of red ginger 20% and garlic 80%) and every treatment there is 4 repetitions, each repetition consisting of 10 duck eggs. The method research was to use organoleptic test on salted eggs on 40 respondents for the judging, The data from the organoleptic test results were calculated using Completely Randomized Design (CRD), if the results of the analysis of variance showed a very real effect, continue using the Duncan Multiple Range Test (DMRT). The research showing that the addition of red ginger and garlic to salted eggs had a very significant effect on the flavour and taste of salted eggs, but not significant effect on the texture and salted eggs sourness. The conclusion of this study is that the best treatment of using red ginger and garlic for salted egg processing is in treatment 2, that is the use of red ginger and garlic as much as 50% seen from the results of the assessment by 40 respondents, then the assessment data were calculated using a completely randomized design. It can be seen from the calculation of data on the RAL that respondents prefer the flavour and taste of salted eggs in treatment 2.